The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.5468/kjog.2012.55.7.534
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Giant Ovarian Cyst Managed Successfully Through Laparoscopic Surgery

Abstract: Mucinous ovarian tumors account for 15% all ovarian neoplasms, of which giant variants rarely occur. Recently huge ovarian cysts (more than 12 kg) are now rarely seen because of the development in health care systems and education. The patient is 26-yearold nulligravida female who presented with abdominal distension. A laparoscopic left salpingo-oophorectomy was performed. Laparoscopic approach to giant ovarian cyst may be difficult regarding the risk of cyst rupture and limited working space. To reduce the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Due to better imaging modalities giant ovarian cyst is a rare finding as diagnosis is made at an early stage. 5 Site of origin of giant intra-abdominal cyst can be ovaries, gastrointestinal region, urological and lymphatics. 6 In 1922 Spohn documented and removed largest ovarian tumour weighing approximately148.6 kg and Symonds in 1963 reported an ovarian cyst of 72 kg.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to better imaging modalities giant ovarian cyst is a rare finding as diagnosis is made at an early stage. 5 Site of origin of giant intra-abdominal cyst can be ovaries, gastrointestinal region, urological and lymphatics. 6 In 1922 Spohn documented and removed largest ovarian tumour weighing approximately148.6 kg and Symonds in 1963 reported an ovarian cyst of 72 kg.…”
Section: Discussionmentioning
confidence: 99%
“…2 Decompression of cyst also helps in prevention of perforation of giant ovarian cyst during trocar insertion and spillage of cyst contents intra-abdominally. 5 Along with benefits of laparoscopic surgery it may also reduce postoperative adhesions which has its own significant benefits like reduction in pelvic pain, improved quality of life and improved fertility especially in case of young unmarried females. 6…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature, to our knowledge, did not define a maximum size of a cyst to be as contraindication for laparoscopic intervention as it is mainly dependent on the experience of the operator. Conservative surgery is always preferred in young females at reproductive age group [21,22] .…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al found that only 0.2% incidence of chemical peritonitis following laparoscopic removal of dermoid cysts. 14 Laparoscopic approach allows proper exposure of Cul de sac and allow forceful jet lavage aspiration ensuring pelvic clean out from any microscopic material of the dermoid cyst. A situation may not be available during open laparotomy.…”
Section: Considerations During Laparotomymentioning
confidence: 99%